Recombinant hepatitis C virus-envelope protein 2 interactions with low-density lipoprotein/CD81 receptors - Urbaczek, Ana Carolina [UNESP]; Ximenes, Valdecir Farias [UNESP]; Afonso, Ana; Generoso, Wesley Cardoso; Nogueira, Camila Tita [UNESP]; Tansini, Aline [UNESP]; Dias Cappelini, Luciana Teresa; Malago Junior, Wilson; Silva, Flavio Henrique da; Fonseca, Luiz Marcos da [UNESP]; Costa, Paulo Inacio da [UNESP] (Fundaco Oswaldo Cruz, 2015)
Hepatitis C virus (HCV) envelope protein 2 (E2) is involved in viral binding to host cells. The aim of this work was to produce recombinant E2B and E2Y HCV proteins in Escherichia coli and Pichia pastoris, respectively, and to study their interactions with low-density lipoprotein receptor (LDLr) and CD81 in human umbilical vein endothelial cells (HUVEC) and the ECV304 bladder carcinoma cell line. To investigate the effects of human LDL and differences in protein structure (glycosylated or not) on binding efficiency, the recombinant proteins were either associated or not associated with lipoproteins before being assayed. The immunoreactivity of the recombinant proteins was analysed using pooled serum samples that were either positive or negative for hepatitis C. The cells were immunophenotyped by LDLr and CD81 using flow cytometry. Binding and binding inhibition assays were performed in the presence of LDL, foetal bovine serum (FCS) and specific antibodies. The results revealed that binding was reduced in the absence of FCS, but that the addition of human LDL rescued and increased binding capacity. In HUVEC cells, the use of antibodies to block LDLr led to a significant reduction in the binding of E2B and E2Y. CD81 antibodies did not affect E2B and E2Y binding. In ECV304 cells, blocking LDLr and CD81 produced similar effects, but they were not as marked as those that were observed in HUVEC cells. In conclusion, recombinant HCV E2 is dependent on LDL for its ability to bind to LDLr in HUVEC and ECV304 cells. These findings are relevant because E2 acts to anchor HCV to host cells; therefore, high blood levels of LDL could enhance viral infectivity in chronic hepatitis C patients.
Keywords: HCV; E2; LDLr; CD81